Predictive indicators of metabolic risk of students of the degree in physical education, recreation and sports at universidad del atlántico (ACTIVIDAD FÍSICA Y DESARROLLO HUMANO, 2023)
Contreras, F., Ramírez, Y. and Padilla, J. (2023). Predictive indicators of metabolic risk in students of the degree in physical education, recreation and sports at the University of Atlántico. The objective of this study was to determine the predictive indicators of metabolic risk factors in university students. For the development of the research, 40 subjects between the ages of 18 and 23, male and female, fourth semester students enrolled in the subject of Sports Biomechanics of the Degree in Physical Education, Recreation and Sports intervened. Data were collected from the anthropometric evaluation (weight, height, diameters, perimeters, and skin folds) as established by the ISAK protocol. It was observed that the age of the sample evaluated has a mean for men of 22.67 ± 4.02 years, for women of 21.30 ± 3.05 years, in relation to the height men present an average of 167.37 ± 36.63 centimeters, women an average of 167.66 ± 6.86; body weight in men an average of 71.99 ± 11.16 kg, in women an average of 65.75 ± 8.0 kg; Regarding the Body Mass Index - BMI, men presented an average of 23.59 ± 3.29 kg/m2, in women an average of 23.32 ± 1.63 kg/m2.
Keywords: Body Mass Index; Waist-Hip Index; Weight; Height; Waist circumference; five masses